2022
DOI: 10.1093/ofid/ofac269
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Retirees Living in Rural Areas: A Poorly Recognized Emerging Problem in Mainland France?

Abstract: Among 40 patients diagnosed with leptospirosis in 3 hospitals of western mainland France between 2014 and 2018 half were at least 60 years old and retired. Their exposure factors were mainly rural residential environment with limited remarkable risk factors. Better awareness and information on leptospirosis appear necessary in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Cases were mainly males 45–64 years of age, and the male-to-female ratio was 3.6:1 [ 3 ]. Studies where disaggregated data were presented usually confirmed an excess in male cases [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…Cases were mainly males 45–64 years of age, and the male-to-female ratio was 3.6:1 [ 3 ]. Studies where disaggregated data were presented usually confirmed an excess in male cases [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%